2007
DOI: 10.1021/jf072612+
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of Luteolin from Peanut Hull Extract Is More Efficient than That from Individual Pure Luteolin

Abstract: Luteoin is one of the main flavones and the crucial effective component of peanut hull extract (PHE). The present paper aims to elucidate the absorption mechanism of luteolin and clarify whether its absorption occurs primarily at a specific site of the intestine by an in situ single-pass intestinal perfusion (SPIP) model. Moreover, the paper investigates the difference in absorption of luteolin when it is administered in PHE form and as pure luteolin by the SPIP model and in vivo pharmacokinetics studies. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 13 publications
3
62
0
Order By: Relevance
“…In addition, there is a possibility that the plasma concentrations of luteolin cannot reach sufficient levels to affect certain gene expression. It has been reported that after administration of 14.3 mg/kg luteolin or 92.3 mg/kg peanut hull extract (equivalent to 14.3 mg/kg luteolin) by oral gavage in rats, the maximum plasma concentration of luteolin reached 1.97 g/ml (6.88 M) or 8.34 g/ml (29.1 M) (40). In the present study, we used different methods to administer luteolin to the mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a possibility that the plasma concentrations of luteolin cannot reach sufficient levels to affect certain gene expression. It has been reported that after administration of 14.3 mg/kg luteolin or 92.3 mg/kg peanut hull extract (equivalent to 14.3 mg/kg luteolin) by oral gavage in rats, the maximum plasma concentration of luteolin reached 1.97 g/ml (6.88 M) or 8.34 g/ml (29.1 M) (40). In the present study, we used different methods to administer luteolin to the mice.…”
Section: Discussionmentioning
confidence: 99%
“…6,[10][11][12][13][14][15][16][17] Moreover, Lu has cytotoxicity in cancer cells or immortalized cells, but not in normal cells, meaning that it has fewer side effects when used in treating cancer. 8,12,18 Yet Lu has some drawbacks, such as poor water solubility (,2 × 10 −2 µmol/mL), 19 low oral absorption, 20 and bioavailability (30.4% in rats), 21 which limit its clinical application. Therefore, it is of interest to promote an injectable aqueous formulation for Lu.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the aglycone of luteolin can be directly absorbed in the intestine through passive diffusion, whereas the glycosides of luteolin will be absorbed after being hydrolyzed in the intestine by microbacteria or lactase phlorizin hydrolase (Shimoi et al, 1998;Sesink et al, 2003;Kottra and Daniel, 2007;Lu et al, 2010). It has been proved that luteolin was mainly absorbed in the jejunum passively in a single-pass perfused rat intestinal model (Zhou et al, 2008), and luteolin was relatively permeable (with a apparent permeability coefficient of 5.8 Ϯ 0.1 ϫ 10 Ϫ6 cm/s) in a Caco-2 cell model (Ng et al, 2004), which indicated moderate (20 -70%) absorption (Yee, 1997). Because of its polyphenol structure, luteolin is a good substrate of uridine diphosphate glucuronosyltransferases and sulfotransferases and mainly undergoes glucuronidation and sulfation during passage through the intestinal mucosa or the liver (Shimoi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%